PENGARUH WAKTU APLIKASI PUPUK HAYATI VP3 DIBANDINGKAN DENGAN EM4 DAN PUPUK NPK TERHADAP PRODUKSI DAN KUALITAS TANAMAN BAYAM MERAH (Amaranthus tricolor L.) - yuliana yuliana; Indiyah Muwarni; Novi Arfarita (AGRONISMA, 2020)
Biofertilizer is a substance that contains living microorganisms that can increase growth and crop production, while also increasing soil fertility. The VP3 biofertilizer used contains three types of soil bacteria, namely free N inhibiting bacteria, phosphate solvent bacteria, and exopolysaccharide-producing bacteria (EPS). The design used in this study was a randomized block design (RBD) consisting of 7 preparations for 3 replications. The treatment of VP3 biofertilizers with compost provides the best production results compared with the help applied NPK fertilizer 100%, but not significantly different from the application of VP3 biofertilizers with compost combined with EM4 fertilizer. VP3 biological fertilizer treatment with compost alone without a combination of NPK fertilizer is more economical for farmers.